Theater and museum leader: Sverdlovsk region in the space of statistical indicators by culture - Vera S. Kharchenko (Управление культурой)
On the basis of official statistics, cultural indicators for 2000-2020 were studied, and the main focus in the analysis of Rosstat information was the study of the dynamics of changes in both all-Russian indicators and data by region. The results of a comparative analysis of statistical indicators in the field of culture in Russia and the Sverdlovsk region showed that theater and museum activities are developed in the region and their visitors are active, and library activity reflects the all-Russian trends in the reduction of infrastructure. The number of theaters in the Sverdlovsk region has remained virtually unchanged over the past 10 years and amounted to 20 theaters, 17 of which are under the jurisdiction of the Ministry of Culture of the Russian Federation. The theaters of the Sverdlovsk region are quite large compared to the average for Russia: they have more seats (453 seats per theater versus 426 in the country as a whole) and more staff (2,393 employees in total, which is approximately 141 people per theater). , and the all-Russian figure is 133 people / theater). Interest in theaters in the Sverdlovsk region is higher than in the country as a whole - in the region there are 314 spectators per 1000 people. population, which is 34 people. more than the corresponding national figure. In the field of library activities in the Sverdlovsk region, there is an all-Russian trend towards a reduction in the number of libraries (by 3 p.p. in the region and 8 p.p. in the Russian Federation in 2010-2020) and the library fund - its volume in 2020 amounted to 77% in relation to the figure for 2000. The reverse trend was recorded in terms of their visits: the number of library users increased over 10 years (1468 thousand people, or 117% in 2019 to 2010), there was an increase in visitors to cultural events (11,227.7 and 11,427.7 in 2018 and 2019, respectively). The museum sphere in the Sverdlovsk region is quite developed and growing: the region is the leader in terms of their number - in 2020 there were 96 museums in total, and their fund increased over 10 years, amounting to 113% by 2010 (the similar all-Russian figure is 118%). On average, 19 employees are employed in one museum, 11 of which are researchers or guides (for the Russian Federation, these figures are 27 and 15 people, respectively). However, the statistics on visiting museums administered by the Ministry of Culture of the Russian Federation indicates a low interest of the inhabitants of the Sverdlovsk region compared to the national data: an average of 21.3 thousand people visit one museum per year, which is significantly lower than the national indicator (45.6 thousand . pers.). Statistics on visiting "non-departmental" museums show a higher demand - one such museum is visited by almost 11 thousand people. per year more than the museums of the Ministry of Culture of the Russian Federation. The article also presents similar indicators and calculations for regions with million-plus cities, which makes it possible to compare cultural consumption practices in regions that are similar in terms of demographic characteristics. The most similar to the Sverdlovsk region in terms of statistical indicators for theaters are the Republic of Tatarstan, Krasnoyarsk Territory, Chelyabinsk, Samara, Nizhny Novgorod, Novosibirsk and Omsk Regions, Perm Territory. In the library sphere, the Novosibirsk, Nizhny Novgorod and Chelyabinsk regions, the Republic of Tatarstan, and the Krasnoyarsk Territory are comparable to the Sverdlovsk Region. Statistics on museum activities show the similarity of the Sverdlovsk region with the republics of Tatarstan and Bashkortostan, Rostov and Nizhny Novgorod regions, Krasnoyarsk and Perm regions. The presented statistical indicators can be used by specialists in the management of culture to assess the dynamics of changes and the prospects for the development of this sphere of society and the state.